Theoretical Proposals for Improving the Noise Immunity of Receiving Multi-Position Signals in Channels with Variable Parameters - S. V. Dvornikov; A. V. Pshenichnikov; A. F. Kryachko; M. R. Bibarsov; G. S. Bibarsova (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. At present, the noise immunity of receiving multi-position signals in channels with variable parameters is improved using various signal structures (SS). In particular, in communication systems and the DVB-T2 television standard, these are quadrature amplitude modulation (QAM) signals with transformed constellation diagrams. However, in practical calculations of communication systems, the existing SS models fail to take into account the random nature of changes in the phases of the transformed signal constellation. This, in turn, leads to a discrepancy between the analytical value of error probability and its real value due to asynchronism in the radio link. The SS model proposed in this paper and the obtained analytical ratio take into account the introduced phase distortions in channels with variable parameters.Aim. Development of theoretical proposals for improving the efficiency of receiving QAM signals in radio channels with variable parameters.Materials and methods. The considered transformed SS model and the resulting analytical relation are described on the basis of communication theory and signal theory in the subject area of noise immunity research methods. This, in turn, enables analysis of the effect of phase distortions in channels with variable parameters on the error probability of receiving QAM signal elements.Results. A transformed SS model with improved energy characteristics and an analytical relation for calculating the error probability of receiving QAM signal elements are proposed. Theoretical proposals for improving the noise immunity of receiving multi-position signals in channels with variable parameters are formulated.Conclusion. The developed theoretical proposals for improving the noise immunity of multi-position quadrature signal structures in channels with variable parameters make it possible to improve their energy characteristics, taking into account phase distortions introduced by the communication channel. The presented dependence makes it possible to evaluate the relationship between the values of the probability of a pair error of receiving QAM signal elements and the limits of the change in phase shifts introduced by a communication channel with variable parameters. Future research will address the development of scientific and practical proposals for improving the noise immunity of quadrature multi-position signals, including an algorithm and block diagram for compensating phase shifts introduced in communication channels; processing of the amplitude values of the signal, which assumes the difference in the paths in terms of frequency-polarization and determines the accuracy of eliminating phase distortions.